The DEAD-box RNA Helicase Dbp2 Connects RNA Quality Control with Repression of Aberrant Transcription - Cloutier, Sara C. (American Society for Biochemistry and Molecular Biology, 2012)
DEAD-box proteins are a class of RNA-dependent ATP hydrolysis enzymes that rearrange RNA and RNA-protein (ribonucleoprotein) complexes. In an effort to characterize the cellular function of individual DEAD-box proteins, our laboratory has uncovered a previously unrecognized link between the DEAD-box protein Dbp2 and the regulation of transcription in Saccharomyces cerevisiae. Here, we report that Dbp2 is a double-stranded RNA-specific ATPase that associates directly with chromatin and is required for transcriptional fidelity. In fact, loss of DBP2 results in multiple gene expression defects, including accumulation of noncoding transcripts, inefficient 3′ end formation, and appearance of aberrant transcriptional initiation products. We also show that loss of DBP2 is synthetic lethal with deletion of the nuclear RNA decay factor, RRP6, pointing to a global role for Dbp2 in prevention of aberrant transcriptional products. Taken together, we present a model whereby Dbp2 functions to cotranscriptionally modulate RNA structure, a process that facilitates ribonucleoprotein assembly and clearance of transcripts from genomic loci. These studies suggest that Dbp2 is a missing link in RNA quality control that functions to maintain the fidelity of transcriptional processes.